Adsorption of heavy metals onto activated carbons derived from polyacrylonitrile fiber - Ahmad Zaini, Muhammad Abbas (Elsevier, 2010)
The aim of this research is to produce activated carbons derived from polyacrylonitrile (PAN) fiber and to examine their feasibility of removing heavy metals from aqueous solution. Thermogravimetric analysis was used to identify the suitable conditions for preparing oxidized fiber and coke as activated carbon precursors. Steam and CO2 were used to activate the precursors. Activated carbons were characterized by their pore texture, elemental compositions and surface functionalities. Batch adsorption and desorption studies were carried out to determine the metal-binding ability of activated carbons. Two commercial activated carbon fibers (ACFs), i.e., A-20 and W10-W, were employed to compare the removal performance of PAN derived activated carbons. Influence of oxidation treatment of PAN fiber prior to steam activation was also explored and discussed. Results indicated that steam produced a higher surface area but a lower resultant yield as compared to CO2. Also, precursors activated by steam showed a greater removal performance. For both activation methods, fiber displayed a better metal-binding ability than coke. A small nitrogen loss from PAN fiber as a result of oxidation treatment assisted a greater removal of Cu(II) and Pb(II), but the interaction to Cu(II) was found stronger. It is proposed that the formation of cyclized structure by oxidation treatment minimized the nitrogen loss during steam activation, hence increased the uptake performance.